The role of mitochondria-derived reactive oxygen species in the pathogenesis of non-steroidal anti-inflammatory drug-induced small intestinal injury. (September 2014) - Handa, O.; Majima, A.; Onozawa, Y.; Horie, H.; Uehara, Y.; Fukui, A.; Omatsu, T.; Naito, Y.; Yoshikawa, T.
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) have been implemented in clinical settings for a long time for their anti-inflammatory effects. With the number of NSAID users increasing, gastroenterological physicians and researchers have worked hard to prevent and treat NSAID-induced gastric mucosal injury, an effort that has for the large part being successful. However, the struggle against NSAID-induced mucosal damage has taken on a new urgency due to the discovery of NSAID-induced small intestinal mucosal injury. Although the main mechanism by which NSAIDs induce small intestinal mucosal injury has been thought to depend on the inhibitory effect of NSAIDs on cyclooxygenase (COX) activity, recent studies have revealed the importance of mitochondria-derived reactive oxygen species (ROS) production, which occurs independently of COX-inhibition. ROS production is an especially important factor in the increase of small intestinal epithelial cell permeability, an early stage in the process of small intestinal mucosal injury. By clarifying the precise mechanism, together with its clinical features using novel endoscopy, effective strategies for preventing NSAID-induced small intestinal damage, especially targeting mitochondria-derived ROS production, may be developed.